Penerapan Model Peers Modeling Motivation Terhadap Motivasi dan Perilaku Makan Sayur pada Anak Usia Pra Sekolah - Nelista, Yosefina; Nona Fembi, Pembronia; Elfi, Teresia (Jurnal Kesehatan, 2023)
Consuming vegetables and fruit is one of the requirements in fulfilling a balanced nutritional menu. Vegetables are very important to be consumed, especially for school-age children. If a child has good eating habits, that is by applying healthy and balanced nutrition from an early age, these habits will have an impact until adult age. One of the efforts that can be done to make children want to consume vegetables is by applying peer modeling motivation. Modeling or imitating behavior is matching or imitating the behavior of others who are considered exemplary and can involve certain symbols. The purpose of this study is to analyze the effect of applying the peer modeling motivation model on the motivation and behavior of eating vegetables in preschool age children. The type of research used was a quasi-experimental research design with one group pretest posttest design. The population in this study were 34 preschool age children. The sampling technique used in this study was purposive sampling technique based on inclusion and exclusion criteria. The sample size in this study was 25 children who did not want to eat vegetables. The results of the Wilcoxon test show that there is an effect of applying the peer modeling motivation model on the motivation and behavior of eating vegetables in preschoolers (p=0.000, p<α, α=0.05). It can be concluded that the application of the peers modeling motivation model can increase the motivation and behavior of eating vegetables in preschoolers.